2020
DOI: 10.37496/rbz4920190145
|View full text |Cite
|
Sign up to set email alerts
|

Association of the forage management practices, weaning rate, and factors that influence technological adoption in beef cattle production

Abstract: The objective of this study was to verify the association of improved native grassland and winter and summer pastures on the weaning rate in beef cattle production. Subsequently, we also verified the socioeconomic and productive characteristics related to the adoption of technologies to increase the weaning rate of the farmers. The survey was conducted with 73 producers of Hereford and Braford cattle in the state of Rio Grande do Sul, Brazil. A data analysis was performed using the minimum ordinal squares meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…However, the decision to adopt any farming-related technology is complicated [ 8 ]. A variety of factors, including socio-demographic features, farm characteristics, economic conditions, and institutional factors, may influence decision making [ [9] , [10] , [11] , [12] ]. As a result, identifying the factors' influencing adoption is critical for the livestock sector's development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the decision to adopt any farming-related technology is complicated [ 8 ]. A variety of factors, including socio-demographic features, farm characteristics, economic conditions, and institutional factors, may influence decision making [ [9] , [10] , [11] , [12] ]. As a result, identifying the factors' influencing adoption is critical for the livestock sector's development.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research revealed that communication between farmers and technicians is essential for the adoption of livestock management practices in Brazil [ 9 , 10 ]. Adoption of ILMP is also influenced by education, cattle number, and information source [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation